Mercedes and the moose test (A) - Diermeier, Daniel, (SAGE Knowledge. Cases., 2017)
The case describes a crisis management situation faced by Mercedes-Benz, a division of Daimler-Benz AG. In 1997 Mercedes introduced a revolutionary new car, the A-class, Mercedes' first entry into the compact car segment. The A-class was positioned as an entry-level vehicle in the Mercedes line and represented Mercedes' attempt to grow beyond its core market. A few days after the car was officially introduced, it rolled-over during a test known as the moose test conducted by a Swedish journalist. The A-class's failed moose-test created extensive media coverage in Germany and other European countries, threatening the success of the A-class launch.